Smart garbage collection management system - Gaddam, Mounica; Dileep Thatha, Venkata; Ravi Kavuluri, Srinivas; Krishna Popuri, Gopi (International Journal of Engineering and Technology, 2018)
Waste management is necessary in today's world because, with the growing population, waste generated by the human is also increasing. Million Tons of waste is being produced by the people all over the world every day. If waste is not properly disposed off, it may lead to huge health issues and it may have adverse effects on our environment also. Among all, waste collection and transportation are one of the costliestÂ stages in solid waste management. As the truck driver must go to each bin every single day and check whether the bin is full or not. If the bin is not full, it is not only waste of time but also wastes of fuel for truck and it also increases pollution due to smoke released from trucks, needs more men for checking all the bins in different routes. In this paper, we are going to propose a smart solution for this problem using the Internet of Things. We use an ultrasonic sensor to measure the size of the bin, and raspberry pi to process the information further. This sensor data will be sent to the cloud using Wi-Fi module of raspberry pi, from the cloud the data is sent to android app. When the trash inside the bin crosses the certain threshold level, that bin and its location are shown in the App using google maps, and the current location of the truck driver is detected, and shortest path is shown. By this the garbage bins can be emptied before the dustbin overflow.